Global Trends in Culturally Responsive Teaching: A Systematic Literature Review - Rofiqi, Ainur; Adhi Suciptaningsih, Oktaviani; Mardhatillah, Mardhatillah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Population growth has led to increasing cultural and ethnic diversity. However, these differences often cause conflict. Therefore, it is essential for individuals to learn to accept diversity as a source of richness and strength in maintaining harmony and cooperation among nations. Misunderstandings may lead to conflict, disharmony, and further miscommunication. One way to address these challenges is through the implementation of Culturally Responsive Teaching (CRT) in education. CRT is an approach that empowers students intellectually, emotionally, and socially through cultural references to convey knowledge, develop skills, and shape behavior. The purpose of this study was to analyze global research trends on CRT during the 2014–2024 period to identify patterns, publication dynamics, and future directions in this field. The results showed a growing trend in the number of publications related to CRT. Most studies involved undergraduate students as participants, with interview sheets being the most commonly used instruments, supported by data analysis based on triangulation. This study provides a theoretical contribution by mapping the direction and development of CRT research globally over the past decade, as well as a practical contribution through policy recommendations aimed at strengthening the implementation of culturally responsive teaching from primary to higher education levels. The findings also offer valuable insights for future CRT implementation and educational policy development.